Possibilities of using three-dimensional optical scanning in complex geometrical inspection - Brajlih, Tomaž (Strojniški vestnik, 2011)
Non-contact optical three-dimensional measuring, scanning and digitising are increasingly present in quality assurance systems. Simple scanning procedures, high density of data acquired in a single scan, and the possibility of integrated reverse engineering and inspection, are all advantages of optical scanning compared to conventional measuring methods. Due to the three-dimensional acquisition of measuring data, an optical scanner is often considered to be an alternative possibility for coordinate measuring machines. However, the accuracy of the measured data acquired by optical scanning (even with a high-end system) is still far below the level achieved by high-level coordinate measuring machines. This paper examines the possibilities of using a three-dimensional scanner for workpiece inspection. The first part presents a special field of workpiece inspection in which, even with currently achievable accuracy, optical scanning is a viable solution for the inspection of manufactured parts. In addition, the achievable dimensional accuracy of an optical scanner is tested by scanning several gaugeblocks. In conclusion, a head to head comparison with a coordinate measuring machine is made by scanning and verifying a sphere.
Keywords: 3D optical scanning; geometry inspection; hitra izdelava; merilna negotovost; povratno inženirstvo; preverjanje geometrije; quality assurance; rapid manufacturing; reverse enginering; trirazsežno optično skeniranje; uncertainty of measurement; zagotavljanje kakovosti